QUANTITATIVE PHYTOCHEMICAL ANALYSIS OF MAULI BANANA STEM AND BASIL LEAVES EXTRACT MIXTURE - A.M. Della Namira Aghnina; Dewi Puspitasari; Yusrinie Wasiaturrahmah (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: Mauli banana stem extract and basil leaves extract are ingredients that has been involved in in vitro and in vivo researches for their pharmacognosy and therapeutic applications. Preliminary phytochemical test of both individual extract revealed the presence of triterpenoid, tannin, phenolic, saponin, steroid, alkaloid, and flavonoid compound. A combination of mauli banana stem and basil leaves extract is believed to work synergistically and may have a more beneficial effect than in single herbal extract. Purpose: To analyze the results of quantitative phytochemical of mauli banana stem and basil leaves extract mixture. Method: Non-experimental research with quantitative laboratory examination to determine sample content. Results: The result showed that mauli banana stem and basil leaves extract mixture contain triterpenoid (30%), saponin (24,75%), flavonoid (15%), alkaloid (22%), phenolic (8%), steroid (4,62%), and tannin (0,03%). Conclusion: Mauli banana stem and basil leaves extract mixture correlated with an increase in majority of the bioactive compound compared to the single extract and would serve as a promising source for phytomedicine. The bioactive compound with the highest content was triterpenoid with 30%, while the lowest was tannin with 0,03%. Keywords: Basil leave extract, Mauli banana stem extract, Quantitative phytochemical test